Why do 'the law' comply? Procedural justice, group identification and officer motivation in police organizations - Bradford, B; Quinton, P; Myhill, A; Porter, G (2014)
How can police officers be encouraged to commit to changing organizational and personal practice? In this paper we test organizational justice theories that suggest that fair processes and procedures enhance rule compliance and commitment to the organization and its goals. We pay particular attention to (a) tensions between the role of group identity in organizational justice models and classic concerns about 'cop culture'; and (b) the danger of over-identification with the organization and the counterproductive types of compliance this may engender. Results suggest that organizational justice enhances identification with the police organization, encourages officers to take on new roles, increases positive views of community policing, and is associated with greater self-reported compliance. Identification with the organization has generally positive implications; however, there is some danger that process fairness may encourage unthinking compliance with orders and instructions. © The Author(s) 2013.